2004
DOI: 10.1126/science.1101617
|View full text |Cite
|
Sign up to set email alerts
|

Avian Extinction and Mammalian Introductions on Oceanic Islands

Abstract: The arrival of humans on oceanic islands has precipitated a wave of extinctions among the islands' native birds. Nevertheless, the magnitude of this extinction event varies markedly between avifaunas. We show that the probability that a bird species has been extirpated from each of 220 oceanic islands is positively correlated with the number of exotic predatory mammal species established on those islands after European colonization and that the effect of these predators is greater on island endemic species. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
658
7
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 735 publications
(692 citation statements)
references
References 14 publications
12
658
7
15
Order By: Relevance
“…Non-migratory and island birds have been suggested to have particularly high extinction risk [39,40]. For island birds (defined here as species with at least 90% of their range on oceanic geological origin or distant continental/ island states), we find these assertions confirmed at the global scale, as they are disproportionately more threatened than expected (17% of island birds versus 8% of mainland birds are threatened; x 2 1 ¼ 109.7, p , 0.01; table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Non-migratory and island birds have been suggested to have particularly high extinction risk [39,40]. For island birds (defined here as species with at least 90% of their range on oceanic geological origin or distant continental/ island states), we find these assertions confirmed at the global scale, as they are disproportionately more threatened than expected (17% of island birds versus 8% of mainland birds are threatened; x 2 1 ¼ 109.7, p , 0.01; table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The loss of anti-predator behaviour in evolutionary time can have important contemporary consequences [23], such as promoting the extinction of prey that have become naive due to the loss of anti-predator behaviour [47]. Because mice do not respond to fox cues on a nearby island that does not contain foxes, but does contain owl predators [29], relaxed selection resulting from loss of fox predators over evolutionary timescales can lead to the lack of a response to fox predators in island mice.…”
Section: Discussionmentioning
confidence: 99%
“…A filter effect occurs when islands that suffered more extinctions of species had fewer remaining rare species that would be listed as being under threat. Past studies have suggested that the numbers of introduced mammalian predators result in a filter effect on the number or proportion of threatened species (Blackburn et al 2004, Trevino et al 2007. Our results revealed the influences of anthropogenic activities on the number of threatened bird species on islands, through direct and indirect influences of human population size on past extinctions and the introduction of mammalian predators.…”
Section: Discussionsupporting
confidence: 55%
“…We began with a large published data set of the richness (i.e., number of species) of avifaunas of 220 oceanic islands (data supplemental to Blackburn et al 2004, original data from Biber 2002), augmented with additional information for 18 (for extinctions) and 21 (for threatened species) of the islands (Trevino et al 2007. Information in the dataset included the area of the islands (viz., island size), distance to a continental mainland, species richness of the original (pre-human colonization) avifaunas, number of humanintroduced mammalian predators, years since historical human colonization of the islands, number of extinctions since historical colonization, and number of currently threatened species (updated from BirdLife International 2012).…”
Section: Methodsmentioning
confidence: 99%